Irish women in business, 1850-1922: navigating the credit economy - Hart, Antonia Florence (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2021)
Irish Women in Business, 1850-1922: navigating the credit economy Antonia Florence Madeleine Jamesie Hart 90408373 Abstract Irish women owned and managed businesses in the late nineteenth and early twentieth centuries, working in sectors that included boarding- and lodging-houses, public houses and spirit grocers, pawnbroking, the tobacco trade, and many more. They operated their businesses in a credit economy where it was usual to balance debt on the one hand with credit on the other. Frequently businesswomen offered credit to their customers while benefiting from credit from their suppliers, and they bridged short-term gaps with cash loans from family and business contacts and goods on credit. When the gaps were impossible to bridge, the consequences of debt, in the form of a legal recovery, or even a petition of bankruptcy, kicked in. Some women benefited from using debt as a tool, as well as suffering under its burden. Women?s business lives were integrated with men?s business lives, and with the social and economic affairs of their locality. Women were not just influenced by their environment and business and family networks, but exerted their own influence. They did this not as moral guardians of home and family, but as employers, innovators, and negotiators. They directly facilitated, through their role in the pawnbroking industry, the functioning of the credit economy. Issues surrounding the respectability of pawnbroking, and the reputations of those who worked in it, did not prevent women in the business from making money and using it to fund comfortable and apparently respectable lives. This research establishes that during the period under examination women could and did act with agency, making economic decisions and operating their own businesses.
APPROVED
Keywords: women; business; Ireland; history; economic history; social history; gender history; women's history; business history; work; enterprise; women entrepreneurs; female entrepreneurs; history of debt; credit economy; early twentieth century; nineteenth century; Irish